Sistem Keamanan Kendaraan Roda Dua Berbasis Internet Of Things (IOT) - Supriatin Atin; Dedy Abdullah; Yulia Darmi; M Husni Rifqo (Jurnal Media Infotama, 2023)
The high rate of theft of two-wheeled vehicles makes vehicle owners afraid to leave their vehicles. Most vehicle owners increase the security of their vehicles by providing a padlock key that is placed on the motorcycle disc.Along with the increasing acts of motorcycle theft, vehicle security must also be improved, so that vehicle owners are not afraid if they have to leave their vehicle. Therefore the author wants to create a security system by utilizing a smartphone as a vehicle control tool remotely. In this study a vehicle security system was designed with fingerprints as keys and realtime monitoring of vehicles via telegram by utilizing Arduino Uno, Relay, FingerPrint Sensor, ESP32 CAM and NodeMCU. This study used an experimental method which directly tested the vehicle. The test was carried out with 10 different fingerprints, 8 finger positions and 5 fingerprint obstacles. The test results show that the system can execute commands with an average delay time of 9.11 seconds and can provide notifications in the form of messages to Telegram and can be monitored in real time when someone tries to activate the vehicle.